Brand love impact on the social media and stages of brand loyalty - Suha, F. S.; Tarofder, Arun Kumar; Adiza, A. M.; Chaichi, Kamelia * (Copernicus, 2019)
The primary objective of the current research is to propose and investigate a conceptual model which integrates social media activities and brand love as antecedents and brand loyalty phases as an outcome of brand love. The proposed model is analysed with a sample of 240 fast fashion’s consumers by using a self -structured questionnaire survey technique. PLS -SEM applied for statistical analysis to evaluate the hypnotized linkage between the variables. The results show that social internet marketing has a tremendous impact on brand love in the fast fashion profession. Furthermore, the finding shows that social media, has an indirect constructive effect on the various phases of brand loyalty through brand love. The current research supports the crucial role of social media in marketing and advertising which will assist internet marketers to fully realize brand love and loyalty behavior. The consequence of this particular study might assist marketers to develop the successful communication approach through social networking activities to shape good attitudes and advance brand loyalty, particularly in fast fashion profession.